A comunicação do religioso: a homilia sob a ótica de leigos e padres - Mourão, Yleris de Cássia de Arruda (2006)
Through the view of lay members, priests and researchers in communication, liturgy and homily, we will seek to present subsidies about the relationship among homily, communication and religion. Initially, we defend the hypothesis that the sermon can be seen as an archaic, tiring and inefficient speech, also poor in communicative elements, mainly in aspects of oratory.The scientific methodology was developed with base in a holistic, qualitative and quantitative perspective. We verified, through the investigation that the homily is still space for construction and re-construction of ethos and world vision. The priest s speech during the homily is still considered effective for great part of the lay members; however, for the priests this efficacy is relative; it depends on a series of factors. These factors will be evidenced in the first chapter, in which we will demonstrate the epistemological categories that appeared in the empiric research. We will verify that the religion has an enormous persuasive power through their symbols, rites and ideologies. In the second chapter, we will know the homily through the eye of the Apostolic Roman Catholic Church. In the third chapter, we will show the phenomenon of the communication and their interfaces: from the language to the aesthetics of the public speaking. In the conclusion, we will demonstrate some aspects that justify the non corroboration of our hypothesis. We explain that the symbolic power is the key word so that the homiletic speech is considered effective on the part of the followers that legitimate it for the faith.